Uji Tingkat Toleransi Tanaman Jagung Pada Fase Tertentu Terhadap Cekaman NaCl pada Tanah Sulfat Masam dengan Budidaya Jenuh Air - sumarti sumarti; Ir. Setia Budi, M.MA Ir. Setia Budi, M.MA; Ir Dini Anggorowati, M.Sc Ir Dini Anggorowati, M.Sc (Jurnal Sains Pertanian Equator, 2016)
Demand of corn always increased. Therefore corn production has to be increased through both intensification and extensification program. Cultivation of corn in acid sulphate soil has salinity problems causing crop toxicity. This study aims to determine the effect of NaCl concentration to the growth and yield of corn in the acid sulphate soil with saturated cultivation, and assesing the growth phase of corn which is tolerant to the NaCI stress. The experiment was carried out at green house, located in Faculty of Agriculture, Tanjungpura University Pontianak. The experimental design was completely randomized design which consisted of two factors and three replications. The first was the level NaCl which consisted of n0 (without NaCI), n1 (1,50+3,00 dS/m) dan n2 (3,00+6,00 dS/m) whereas the second factor was NaCl application time which consisted of p1  (early growth phase), p2 (toward tasseling phase), and p3 (after tasseling phase). The result showed that the treatment of NaCI concentration sinivicantly effeced only the dry wight of plant. Meanwhile, the period of NaCI application did not effect on all variable observed.